Insight into forensic efficiency and genetic structure of the Guizhou Dong group via a 64-plex panel - Wan, Wen; Ren, Zheng; Zhang, Hongling; Wang, Qiyan; Wang, Ting; Yang, Yunteng; You, Jiangtao; He, Kun; Huang, Jiang; Jin, Xiaoye (Frontiers in Ecology and Evolution, 2023)
Insertion/deletion polymorphisms (InDels) show great application values in forensic research because they own superiorities of short tandem repeats (STRs) and single nucleotide polymorphisms (SNPs). Whereas, InDels commonly display low genetic diversities in comparison to STRs. Therefore, they may provide limited genetic information in forensic kinship testing. Here, we evaluated forensic application efficiency of a novel multiplex amplification system including two STRs, 59 InDels, and three sex-determination loci in the Guizhou Dong group. In addition, we explored the genetic background of the Guizhou Dong group in comparison to other reported populations based on 59 InDels. We found that 59 InDels displayed relatively high genetic diversities in the Guizhou Dong group. Moreover, the cumulative forensic efficiency of two STRs and 59 InDels could meet the requirement of individual identification and paternity testing in the Guizhou Dong group. For these 59 InDels, we observed that some loci exhibited relatively high genetic differentiations among different continental populations, especially for African and Non-African populations, which could be viewed as candidate ancestry informative markers in the future. Genetic structure results indicated that the Dong group had close genetic relationships with East Asian and some Southern Chinese Han populations. To sum up, we stated that the 64-plex panel could be performed for forensic application of the Guizhou Dong group.